KINERJA PENYULUH PERTANIAN DI MASA PANDEMI COVID-19 DI KECAMATAN LANGOWAN BARAT KABUPATEN MINAHASA (Performance of Agricultural Extension Workers During The Covid-19 Pandemic in West Langowan Sub District Minahasa Regency) - Yohana Dikna Suwuh; Yolanda P. I. Rori; Agnes E. Loho (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The objective of this research is to determine how the performance of agricultural extension workers during the Covid-19 pandemic in West Langowan Sub District. This research was conducted from March to June 2021. The data collected in this study were primary data sourced from observations and direct interviews with respondents in the form of a list of questions (questionnaires). Analysis of the data used in this study is descriptive analysis, and to determine the level of performance of agricultural instructors used a Likert scale. The research results showed that the level of performance of agricultural extension workers in West Langowan District during the Covid-19 pandemic was relatively high, measured from the preparation, implementation, evaluation and reporting of extension. Extension activities during the Covid-19 pandemic, agricultural extension workers continue to carry out counseling such as direct visits to farmers. Changes in extension activities, namely mass counseling have been reduced, the frequency of visits to farmers is limited, the distribution of material is minimized and using via telephone (WhatsApp/Zoom) for coaching methods.